The Impact of Social Media On The Gastronomy Business - Bela, Tresna; Ahmad Hudaiby Galih Kusumah; Riche Cynthia Johan (Journal of Tourism Sustainability, 2024)
This study examines the effectiveness of marketing strategies deployed on social media platforms such as Facebook, Instagram, and Twitter, highlighting their critical role in driving sales and enhancing visibility for gastronomy businesses in the digital era. Social media enables direct customer interaction, providing business owners with valuable feedback and opportunities to foster strong relationships, ultimately increasing customer loyalty. The research emphasizes the significance of analyzing customer sentiment and exploring key factors influencing consumer behavior, including the impact of influencers and user engagement on these platforms. Findings reveal that prior experiences and consumer knowledge significantly shape gastronomic preferences and decisions, demonstrating the powerful influence of social networks on consumer behavior. By identifying essential elements and adopting data-driven marketing strategies, gastronomy businesses can attract and retain customers while promoting their products. This study employs a systematic literature review (SQLR) methodology to offer a comprehensive understanding of the role of social media in the gastronomy industry, providing actionable insights for practitioners and scholars alike.